Asymptotic optimal method for localisation of a target in wireless sensor networks. (22nd June 2009) - Lim, Jaechan; Lee, Jinseok
In this paper, we present a location estimation method based on received signal strength (RSS) measurement or observation equation. The practical maximum likelihood (ML) estimator is asymptotically optimal in the sense it is asymptotically minimum variance unbiased (MVU) estimator and efficient estimator. We apply ML method to locating a target using multiple measurements where especially, numerical method is required. We employ two types of 'initial guesses' based on least squares (LS) method before initiating the iterative ML method in this paper. We show the performances comparison of a number of methods to achieve the optimal solution. The practical problems our approach can be applied to are 'localising mobile phones using multiple base stations' or 'localising wireless sensors using multiple anchor sensor nodes', etc.